Técnicas de estudio para mejorar el rendimiento escolar en el área de lengua y literatura de los estudiantes del tercer grado de educación básica, paralelo B, de la escuela Eliseo Álvarez, año lectivo 2014-2015 - Gonzales Salinas, Gabriela Elizabeth (2016)
This research work called study techniques to improve school output in the area of language and Literature of the students, from the third grade of Basic Education, parallel B, of the Eliseo Alvarez School, school year 2014-2015. The general objective of this investigation is to apply study techniques to improve school performance in the area of language and literature of the students from the third grade of General Basic Education parallel B of the Eliseo Alvarez School. The specific objectives have to do with the theoretical and scientific basis of study techniques and school performance, to diagnose the study techniques that are implemented and what is the children’s school performance; to design study techniques to improve the academic performance of students; to implement and to evaluate study techniques which contributes to the improvement of the education results. The design type was quasi-experimental and transversal developed by the researcher to solve the difficulties found in school performance. Also it was descriptive and field investigation for recovery of empirical information that contributed to the explanation of the variables and indicators of the study object. In the methodology, the analytical method was used to undo the variables that are involved in the research and the method that allowed covering the interpretation phase of the empirical data during the field work. The survey technique was applied to the teacher and 29 students, obtaining as results of the research that most students and the teacher were unaware of study techniques as tools for the study, therefore in this frame the research concludes that the application of the alternatives through the workshop has positive results in the solution of the problems that students faced in the classes.